Zakrzep zagrażający żyły środkowej siatkówki w przebiegu guza jelita grubego i nerki – trudności diagnostyczne - Tonderska, Małgorzata; Ciszewska, Joanna; Dróbecka-Brydak, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Central retinal vein occlusion (CRVO) is one of the commonest ophthalmic diseases of vascular background following systemic disorders. The complex etiology of the disease is often responsible for difficulties in establishing diagnosis. Trousseau was the first to describe in 1865 the increased risk of venous thrombosis in cancer patients. Segev et al. published the case of bilateral CRVO and colon cancer, which was not previously recognized. Another case of a patient with early symptoms of CRVO and generalized neoplastic disease, was identified in Department of Ophthalmology of Warsaw Medical University.